A recent update on development, synthesis methods, properties and application of natural products derived carbon dots - Soumitra Sahana; Anupam Gautam; Rajveer Singh; Shivani Chandel (Natural Products and Bioprospecting, 2023)
Abstract Natural resources are practically infinitely abundant in nature, which stimulates scientists to create new materials with inventive uses and minimal environmental impact. Due to the various benefits of natural carbon dots (NCDs) from them has received a lot of attention recently. Natural products-derived carbon dots have recently emerged as a highly promising class of nanomaterials, showcasing exceptional properties and eco-friendly nature, which make them appealing for diverse applications in various fields such as biomedical, environmental sensing and monitoring, energy storage and conversion, optoelectronics and photonics, agriculture, quantum computing, nanomedicine and cancer therapy. Characterization techniques such as Photoinduced electron transfer, Aggregation-Induced-Emission (AIE), Absorbance, Fluorescence in UV–Vis and NIR Regions play crucial roles in understanding the structural and optical properties of Carbon dots (CDs). The exceptional photoluminescence properties exhibited by CDs derived from natural products have paved the way for applications in tissue engineering, cancer treatment, bioimaging, sensing, drug delivery, photocatalysis, and promising remarkable advancements in these fields. In this review, we summarized the various synthesis methods, physical and optical properties, applications, challenges, future prospects of natural products-derived carbon dots etc. In this expanding sector, the difficulties and prospects for NCD-based materials research will also be explored.